Analytical methods and experimental quality in studies targeting carbonyls in electronic cigarette aerosols - Sussman, Roberto A.; Sipala, Federica Maria; Ronsisvalle, Simone; Soulet, Sebastien (Frontiers in Chemistry, 2024)
We provide an extensive review of 14 studies (11 independent and three industry-funded) on emissions generated by Electronic Cigarettes (ECs), specifically focusing on the evaluation of carbonyls present in these emissions and emphasizing a meticulous evaluation of their analytical methods and experimental procedures. Since the presence of carbonyl by-products in EC aerosol is concerning, it is important to evaluate the reliability of emission studies quantifying these compounds by verifying their compliance with the following criteria of experimental quality: authors must 1) supply sufficient information on the devices and experimental procedures to allow for potentially reproducing or replicating the experiments, 2) use of appropriate puffing protocols that approach consumer usage as best as possible, 3) use of appropriate analytical methods and 4) usage of blank samples to avoid false positive detection. Outcomes were classified in terms of the fulfilment of these conditions as reliable in seven studies, partially reliable in five studies, and unreliable in two studies. However, only five studies used blank samples and six studies failed the reproducibility criterion. Carbonyl yields were far below their yields in tobacco smoke in all reproducible studies, even in the partially reliable ones, thus supporting the role of ECs (when properly tested and operated) as harm reduction products. This review highlights the necessity to evaluate the quality of laboratory standards in testing EC emissions to achieve an objective assessment of the risk profile of ECs.